2016
DOI: 10.1002/chem.201601351
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough in Xenon Capture and Purification Using Adsorbent‐Supported Silver Nanoparticles

Abstract: Rare gas capture and purification is a major challenge for energy, environment, and health applications. Of utmost importance for the nuclear industry, novel separation processes for Xe are urgently needed for spent nuclear fuel reprocessing and nuclear activity monitoring. The recovered, non-radioactive Xe is also of high economic value for lighting, surgical anesthetic, etc. Here, using adsorption and breakthrough experiments and statistical mechanics molecular simulation, we show the outstanding performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
4
33
0
1
Order By: Relevance
“…Metal NPs encapsulated in hollow microporous silica crystals represent a very interesting class of nanomembrane reactors in which the reaction is essentially governed by the permeability of the shell (Farrusseng & Tuel, ). These nanocatalysts are the subject of continuous development for applications such as nuclear waste treatments or selective heterogeneous catalysis (Deliere et al ., ; http://www.molecularproducts.com/us/ionex.htm). Indeed, particles are only accessible to molecules that can diffuse through the zeolite walls, that is with a kinetic diameter smaller than the pore size.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Metal NPs encapsulated in hollow microporous silica crystals represent a very interesting class of nanomembrane reactors in which the reaction is essentially governed by the permeability of the shell (Farrusseng & Tuel, ). These nanocatalysts are the subject of continuous development for applications such as nuclear waste treatments or selective heterogeneous catalysis (Deliere et al ., ; http://www.molecularproducts.com/us/ionex.htm). Indeed, particles are only accessible to molecules that can diffuse through the zeolite walls, that is with a kinetic diameter smaller than the pore size.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…4,58 This is further supported by the slight increase of separation factor with temperature, which is the result of a stronger reduction in Xe adsorption because of its higher heat of adsorption than that of CO 2 . 4 The same situation applies for Kr/Xe separation in other nanoporous crystalline membranes, such as ZIF-8 and SAPO-34, as elucidated by molecular simulation. 60…”
Section: Resultsmentioning
confidence: 81%
“…They demonstrated that the xenon bed could be regenerated after a heat treatment of 200-250°C. In studies in the Farrusseng laboratory (Daniel et al, 2013;Deliere et al, 2016), Ag-exchanged ZSM-5 zeolites showed promise for noble gas capture and separation and performed better than several MOFs evaluated head-to-head along with the zeolites. MOFs are composed of organic moieties interlinked by metal ions or clusters forming a three-dimensional (3D) crystal structure with long-range order.…”
Section: Solid Sorbents For Noble Gas Capturementioning
confidence: 99%